Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A revised Proterozoic tectono-stratigraphy of the South Nicholson region, Northern Territory, Australia—insights from SHRIMP U–Pb detrital zircon geochronology - C. J. Carson; N. Kositcin; J. R. Anderson; P. A. Henson (Australian Journal of Earth Sciences, 2026)

Shale brittleness within the Paleoproterozoic Isa Superbasin succession in the South Nicholson region, Northern Australia - A. H. E. Bailey; A. J. M. Jarrett; L. Wang; B. L. Reno; E. Tenthorey; C. Carson; P. Henson (Australian Journal of Earth Sciences, 2026)

Belowground performance of novel short-stature maize under varying nitrogen rates across contrasting soil types - Binod Joshi; Raziel A. Ordóñez; Daniel Quinn; Chad Penn; Carson Pearl; Tony J. Vyn; Yichao Rui (Field Crops Research, 2026)

Lag in Effective Population Size Decline Amid Demographic Collapse: A Case Study of the Delta Smelt ( Hypomesus transpacificus ) - Amanda J. Finger; Melanie E. F. LaCava; Evan W. Carson; James A. Hobbs; Tien‐Chieh Hung; Matthew L. Nobriga; Leo Polansky; Robin S. Waples (Molecular Ecology, 2026)
Effective population size ( N e ), census size ( N c ) and their ratio ( N e / N c ) are widely used indicators in conservation genetics, yet long‐term empirical data tracking of all three metrics over long time scales in wild populations remains rare. Using monitoring data from 1995 to 2020, we examined temporal dynamics of N e , N c and their relationship during the demographic collapse of Delta Smelt ( Hypomesus transpacificus ), an endangered fish endemic to the San Francisco Estuary, California, USA. We estimated N e for 21 annual cohorts using restriction site‐associated DNA sequencing data, applying the linkage disequilibrium method, temporal method and a recently developed combined method. Abundance was represented by model‐based survey indices ( N c *). N e varied substantially through time (145–1928), declining in recent years but remaining above commonly cited conservation thresholds for long‐term persistence (e.g., N e > 500) until the final years of collapse. N e was positively correlated with N c * ( r = 0.58), but the shallow slope (β = 0.25) indicates that demographic decline outpaced genetic decline. N e / N c * was consistently low (0.0001–0.056), but it increased significantly through time. Our results show that genetic erosion may lag behind demographic collapse and that N e / N c * is not constant and therefore cannot be easily inferred from either variable alone. This study demonstrates the need for additional empirical data sets to facilitate interpretation of N e , N c * and N e / N c * for the conservation of global biodiversity.

Proposed key characteristics of neurotoxic chemicals - Pamela J. Lein; Aaron B. Bowman; Zhengyu Cao; Monica Carson; Brenda Eskenazi; Ellen Fritsche; G. Jean Harry; Thomas Hartung; Isaac N. Pessah; William Slikker; Lauren Zeise; Martyn T. Smith (NeuroToxicology, 2026)

Inter-method differences (SIMS vs. IRMS) in oxygen isotope fractionation: insights from Chinook salmon otoliths - Kohma Arai; Malte Willmes; George E. Whitman; Kenneth W. Zillig; Cassidy J. Cooper; Nozomi Matsuda; Elizabeth A. Bell; Kevin D. McKeegan; Levi S. Lewis; Carson A. Jeffres; Rachel C. Johnson (Geochimica et Cosmochimica Acta, 2025)

Ion exchange and bioregeneration by partial nitritation/anammox for mainstream municipal wastewater treatment - Sheyla Chero-Osorio; Lanica Steele; Valerie Carson; Ananda S. Bhattacharjee; Meng Wang; John Kuhn; Sarina J. Ergas (Bioresource Technology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

A Complicated History of Mitogenome Introgression Among Luxilus Species (Teleostei, Family Leuciscidae) in the Ozark Highlands - David D. Duvernell; Carson Arnold; Shila Koju; Abby J. Wicks; Thomas E. Dowling (Fishes, 2025)
Hybridization is common among minnows and shiners in the family Leuciscidae, and mitonuclear discordance can reveal evidence of historical hybridization and introgression events that have shaped extant species and populations. We have identified a notable case of serial mitogenome replacement in populations of two shiner species, Luxilus zonatus and L. chrysocephalus, which are syntopic in drainages throughout the northern and eastern Ozark Interior Highlands of North America. These mitogenome replacement events involved L. zonatus acquiring the mitogenome of L. chrysocephalus, and populations of L. chrysocephalus acquiring the mitogenome of an allopatric congeneric species, L. cornutus. The latter species has a more northern distribution that was likely shifted southward by glacial advances during the Pleistocene. The geographic extent of mitogenome replacements in both species spans multiple separate drainages encompassing most of the major river systems that comprise the northern and eastern Ozark Highlands. We attribute these patterns to shifting species distributions, which were impacted by multiple glacial advances and coincident geomorphological changes to Ozark Highland drainages throughout the Pleistocene. The serial nature of mitogenome replacements in L. zonatus and L. chrysocephalus may exclude a role for natural selection in these introgression events, but the dynamic shifts in species distributions and gene flow connections throughout the Pleistocene may have favored an invasion-with-hybridization model that predicts massive asymmetric introgression between invading and resident species. These results have applied significance for eDNA metabarcoding methods of biodiversity assessment in Ozark streams, as they are dependent on mitogenome detections.

Diamondback Terrapin Resource Use in a Seagrass-Dominated Coastal Bay Varies by Life Stage - Margaret M. Lamont; Carson Arends; Daniel J. Catizone; Hannah B. Vander Zanden (Estuaries and Coasts, 2025)
Diamondback terrapins, hereafter referred to as terrapins, are the only estuarine turtle species native to North America. However, terrapins are also occasionally found in marine habitats, such as seagrass beds, and yet little is known about how they use those marine habitats. We sampled epidermis from terrapins ( Malaclemys terrapin macrospilota ) inhabiting a seagrass-dominated coastal bay in Northwest Florida and compared resource use among terrapin sexes and life-history stages using the isotopic niche and mixing models. Terrapins were generalist foragers, and their diets varied by sex and life stage, as has been reported elsewhere. Basal resource mixing models indicated the terrapin food web was based primarily on Thalassia testudinum for adult females (50.0%) and Spartina alterniflora for adult males (49.7%) and juvenile females (42.2%). Dietary mixing models indicated the adult female diet included a relatively high proportion of Thalassia testudinum (31.3%), suggesting a strong reliance on seagrass dominated prey and not necessarily large consumption of seagrass, followed by lower proportions of gastropods (26.6%) and crustaceans (19.1%). Primary diet items for juvenile females and adult males included relatively equal proportions of echinoderms, gastropods, crustaceans, ascidians, and porifera. Body and head size of terrapins may drive differences in diet, as interpreted from mixing model results. Although mangroves are expanding their range northward along the Gulf of America coast and have become established at our study site, it does not appear that terrapins are foraging within these newly established mangrove forests. Finally, the terrapin niche, particularly for adult females, may overlap with the sea turtle niche in seagrass-dominated bays. Whether sea turtles impact terrapin populations, including through direct predation, is unknown.

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Impact of sarcopenia and obesity on skeletal muscle size, gene expression, and mitochondrial function - Hector G. Paez; Christopher R. Pitzer; Jessica L. Halle; Peter J. Ferrandi; James A. Carson; Junaith S. Mohamed; Stephen E. Alway (GeroScience, 2025)
Skeletal muscle is a primary tissue of dysfunction during both aging and obesity. Recently, the coincidence of obesity and aging has gained attention due to the intersection of the obesity epidemic with an aging demographic. Both aging and obesity are associated with marked defects in skeletal muscle metabolic health. Despite these findings, we have a poor understanding of how obesity and aging may interact to impact skeletal muscle mass and metabolic health. Therefore, we investigated the impact of high-fat diet (HFD)-induced obesity on skeletal muscle mass, mitochondrial function, transcriptomics, and whole-body metabolism in young and aged mice. We observed main effects of diet and age on several measures of whole-body metabolic function (VO 2 , VCO 2 , and RER). Complex I-driven mitochondrial proton leak was significantly elevated by HFD-induced obesity across both age groups; however, a main effect of aging for reduced complex I leak was detected in the soleus muscle. Interestingly, aged animals fed a HFD did not exhibit lower muscle mass than chow-fed young animals, but did present with stark increases in muscle triglyceride content and a unique transcriptional response to HFD. HFD-induced obesity impacted the muscle transcriptome differently in the muscles of young and aged mice, indicating that obesity can change altered gene expression with age. Our findings suggest that the presence of obesity can both compound and counteract age-associated changes to muscle mass, gene expression, and mitochondrial function.

Functional brain network correlates of cardiorespiratory fitness and moderation by depression symptoms - Lauren R. Borrell; Andrew C. Venezia; J. Carson Smith (Brain Structure and Function, 2025)
Cardiorespiratory fitness may protect against or alleviate depression through neuroplastic mechanisms within disrupted brain networks underlying cognitive and affective symptoms. There is a scarcity of research examining the effects of cardiorespiratory fitness on functional brain networks in representative samples spanning adulthood. Further, little is known about the interaction of cardiorespiratory fitness with depression in these networks. To address this problem, this study made use of the NKI-Rockland sample dataset and magnetic resonance imaging to examine whether functional brain network features associated with cardiorespiratory fitness were moderated by depression symptom severity in a community sample of 217 participants (134 females, 83 males) between the ages of 18 and 71 ( M = 43.8 years, SD = 16.2). Cardiorespiratory fitness was positively associated with whole-brain modularity, between-network connectivity of the central executive and salience networks, and within-network connectivity of the default mode, central executive, and salience networks. The association of cardiorespiratory fitness and default mode network connectivity was stronger in the presence of moderate-to-severe depression symptoms. Taken together, these observations lend support to prior work that has demonstrated the associations of cardiorespiratory fitness with reduced concurrent and prospective depression risk and symptom severity. Depression symptoms moderated default mode network connectivity, suggesting that cardiorespiratory fitness may differentially impact neural substrates for those with moderate-to-severe depression symptoms.

Genomics and serotyping of Tenacibaculum maritimum outbreak isolates from Australia and New Zealand for guided vaccine development and stewardship - O. Rudenko; C. Angelucci; K. Kumanan; L. Delisle; J. Carson; R.N. Morrison; K.S. Hutson; A.C. Barnes (Aquaculture, 2025)

Caught in headlights: Captive white-tailed deer responses to variations in vehicle lighting during imminent collision scenarios - Carson J. Pakula; Gino J. D'Angelo; Adrianna Mowrer; Olin E. Rhodes; Travis L. DeVault (Applied Animal Behaviour Science, 2025)

Impact of climate change on the nitrogen budget of a dairy farm in the Fraser Valley, British Columbia, Canada - Sarah J. Pogue; Marcos R.C. Cordeiro; Alan Rotz; Carson Li; Roland Kröbel; Karen A. Beauchemin; Derek Hunt; Shabtai Bittman (Agricultural Systems, 2025)

Experimental Challenge of Chinook Salmon ( Oncorhynchus tshawytscha ) With Tenacibaculum maritimum and Tenacibaculum dicentrarchi Fulfils Koch's Postulates - Karthiga Kumanan; Jeremy Carson; Ryan B. J. Hunter; Anne Rolton; Ulla von Ammon; Chaya Bandaranayake; Connie Angelucci; Richard N. Morrison; Seumas P. Walker; Jane E. Symonds; Kate S. Hutson (Journal of Fish Diseases, 2025)
The bacterial skin disease tenacibaculosis, caused by Tenacibaculum species, affects numerous economically important marine fish, including salmonids. This study reports the ability of three Tenacibaculum maritimum strains, belonging to different molecular O‐AGC types, and a single Tenacibaculum dicentrarchi strain to induce tenacibaculosis in farmed Chinook salmon ( Oncorhynchus tshawytscha , Walbaum 1792) in Aotearoa New Zealand. Naïve Chinook salmon were exposed to T. maritimum (2 × 10 8 cells/mL) and T. dicentrarchi (2 × 10 7 cells/mL) by immersion using natural seawater. Clinical signs of tenacibaculosis were apparent in all T. maritimum strains used in the challenged fish. Of these, 100% of the fish challenged with O‐AGC Type 2‐1 and Type 3‐2 strains became moribund, whereas only 60% of the O‐AGC Type 3‐0 challenged fish became moribund. Fish exposed to T. dicentrarchi showed more severe symptoms, exposing musculature in 51% of the challenged population, with 28% of fish becoming moribund. Gross pathological signs of fin rot, scale loss, skin ulcers and haemorrhagic skin spots were observed for both Tenacibaculum species and were consistent with those observed on farmed fish. Pure T. maritimum and T. dicentrarchi cultures were reisolated from epidermal damage of challenged fish. Tenacibaculum species was not isolated from the anterior kidney of affected fish, which indicates no systemic infection in Chinook salmon.

A global survey for dust devil vortices on mars using MRO context camera images enabled by neural networks - Susan J. Conway; Valentin T. Bickel; Lori K. Fenton; Manish R. Patel; Helen C. Carson; Antoine Blouin; Justin Crevier; Evan Blanc; Bao Nhi Nguyen; James A. Holmes; Brian Jackson; Lonneke Roelofs (Planetary and Space Science, 2025)

Springtime upwelling conditions influence microbial communities and dissolved thiamin compounds in the California Current Ecosystem - Kelly C. Shannon; Gillian St. John; Robin Gould; Christopher Hartzell; Hailey Matthews; Elizabeth J. Brennan; Luis M. Bolaños; Steven T. Lindley; John C. Field; Nate Mantua; Rachel Johnson; Carson Jeffres; et al. (Limnology and Oceanography, 2025)
Understanding dissolved concentrations of the essential coenzyme thiamin (vitamin B 1 ) can provide insights into the biological controls on highly productive upwelling systems such as the California Current Ecosystem. To connect thiamin availability with microbial communities in the California Current Ecosystem, we measured concentrations of dissolved thiamin and its biochemically related moieties (thiamin congeners) and 16S rRNA gene‐based microbial communities during the spring. We found that strong upwelling caused a depletion of dissolved thiamin precursor compounds and abiotic degradation products relative to periods of weak upwelling. Specific microbial taxa, including species of SAR11 ecotypes, Candidatus Nitrosopumilus, and SUP05 cluster, were also significantly enriched with strong upwelling. Our data provide evidence that alterations to microbial communities in the mixed layer that occur as a result of upwelling could constrain the availability of dissolved thiamin and its chemical congeners in the California Current Ecosystem.

Dynamics of hydrogen–ammonia–natural gas lean-premixed high-pressure flames - Tristan T. Shahin; Alexander J. Hodge; Benjamin K. Murdock; Thomas N. McLean; Keaton C. Koenig; Rohan M. Gejji; Robert P. Lucht; Carson D. Slabaugh (Fuel, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Commercial bacteriophage preparations for the control of Listeria monocytogenes and Shiga toxin-producing Escherichia coli in raw and pasteurized milk - Emily Everhart; Sarah Carson; Kathleen Atkinson; Dennis J. D'Amico (Food Microbiology, 2025)

Optimising Outbreak Investigation, Surveillance and Discovery of Pathogens in Aquaculture Using Unbiased Metatranscriptomics - Vincenzo A. Costa; Richard J. Whittington; Charles Caraguel; Joy A. Becker; Kerrie E. Wiley; Christine Huynh; Jeremy Carson; Francisca Samsing (Reviews in Aquaculture, 2025)
Emerging infectious diseases are a major threat to global aquaculture production and are projected to increase in frequency due to anthropogenic stressors and climate change. Our ability to screen the global aquatic ‘infectome’ is dramatically improving through unbiased metatranscriptomic (i.e., total RNA) sequencing. Despite recent advances in molecular diagnostics and next‐generation sequencing, outbreak investigation in aquaculture often encounters limitations due to the targeted nature of conventional techniques, which may only capture a small portion of the diverse array of disease‐causing agents present in nature, sometimes requiring years to resolve. Here, we propose that unbiased metatranscriptomic sequencing serves as a cost‐effective and powerful technique for characterising pathogens during disease outbreaks and in surveillance programmes. In doing so, we offer a diagnostic framework to mitigate infectious disease threats to global aquaculture. We emphasise the importance of combining rapid metatranscriptomics with traditional techniques for a holistic examination of the causes of unknown aetiologies in aquatic animals, and how it can be used to examine host responses in parallel with pathogen discovery. We suggest that the integration of metatranscriptomics into aquaculture will require upskilling, proficiency testing, user‐friendly bioinformatic tools and open data sharing. Furthermore, it is essential to establish a reporting framework—with analytical guidelines—that ensures the protection of animal industries while safeguarding trade interests.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Internal sand bank seismic stratigraphy provides insight into paleo-barrier island preservation - Carson B. Miller; John A. Goff; Sean P.S. Gulick; Davin J. Wallace; Christopher M. Lowery (Marine Geology, 2024)

Native tree species prosper while exotics falter during gap-phase regeneration, but only where deer densities are near historical levels - Anthony C. Yacucci; Walter P. Carson; Jenna C. Martineau; Curtis D. Burns; Brian P. Riley; Alejandro A. Royo; Thomas P. Diggins; Ian J. Renne (New Forests, 2024)

Targeted recreational hunting can reduce animal-vehicle collisions and generate substantial revenue for wildlife management agencies - Zackary J. Delisle; Carson J. Reeling; Joe N. Caudell; Emily B. McCallen; Robert K. Swihart (Science of The Total Environment, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Effect of fuel temperature on the structure of a high-pressure liquid-fueled swirl flame - John J. Philo; Tristan T. Shahin; Colin T. McDonald; Rohan M. Gejji; Robert P. Lucht; Carson D. Slabaugh (Fuel, 2023)

Basal forebrain functional connectivity as a mediator of associations between cardiorespiratory fitness and cognition in healthy older women - Junyeon Won; Laszlo Zaborszky; Jeremy J. Purcell; Sushant M. Ranadive; Rodolphe J. Gentili; J. Carson Smith (Brain Imaging and Behavior, 2023)

Driving in the dark: Deciphering nighttime driver detection of free-ranging roadside wildlife - Carson J. Pakula; Shane Guenin; Jonathon Skaggs; Olin E. Rhodes Jr.; Travis L. DeVault (Transportation Research Part D: Transport and Environment, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Acardius acephalus in an aborted lamb - A. Morey Matamalas; F. Ridout; J. Dubuc; C. Bianco; R. Reichel; A. Carson (Journal of Comparative Pathology, 2023)

Associations between demographic and parental factors and infant sleep characteristics - Zhiguang Zhang; Brittany A. Matenchuk; Rachel J. Skow; Margie H. Davenport; Valerie Carson (Sleep and Biological Rhythms, 2023)

The resting serum metabolome in response to short-term sprint interval training - Ian A. J. Darragh; Tom P. Aird; Aifric O’Sullivan; Brendan Egan; Brian P. Carson (European Journal of Applied Physiology, 2023)

Multiple trophic pathways support fish on floodplains of California's Central Valley - Bobby J. Nakamoto; Carson A. Jeffres; Nicholas J. Corline; Mollie Ogaz; Christina J. Bradley; Joshua H. Viers; Marilyn L. Fogel (Journal of Fish Biology, 2023)
We used compound‐specific isotope analysis of carbon isotopes in amino acids (AAs) to determine the biosynthetic source of AAs in fish from major tributaries to California's Sacramento‐San Joaquin river delta ( i . e ., the Sacramento, Cosumnes and Mokelumne rivers). Using samples collected in winter and spring between 2016 and 2019, we confirmed that algae are a critical component of floodplain food webs in California's Central Valley. Results from bulk stable isotope analysis of carbon and nitrogen in producers and consumers were adequate to characterize a general trophic structure and identify potential upstream and downstream migration into our study site by American shad Alosa sapidissima and rainbow trout Oncorhynchus mykiss , respectively. However, owing to overlap and variability in source isotope compositions, our bulk data were unsuitable for conventional bulk isotope mixing models. Our results from compound‐specific carbon isotope analysis of AAs clearly indicate that algae are important sources of organic matter to fish of conservation concern, such as Chinook salmon Oncorhynchus tshawytscha in California's Central Valley. However, algae were not the exclusive source of energy to metazoan food webs. We also revealed that other sources of AAs, such as bacteria, fungi and higher plants, contributed to fish as well. While consistent with the well‐supported notion that algae are critical to aquatic food webs, our results highlight the possibility that detrital subsidies might intermittently support metazoan food webs.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Phase II MS4 challenges: moving toward effective stormwater management for small municipalities - Leslie Rieck; Craig Carson; Robert J. Hawley; Madison Heller; Mike Paul; Mateo Scoggins; Mel Zimmerman; Robert F. Smith (Urban Ecosystems, 2022)
Federal regulations for municipal separate storm sewer systems (MS4s) in the United States have been in place since 1990 as part of the Nation Pollutant Discharge Elimination System (NPDES), aiming to reduce sediment and pollutant loads originating from urban areas. However, small-municipality (Phase II) MS4s frequently grapple with several challenges, resulting in a lack of stakeholder buy-in and actionable stormwater management plans. We identify five common challenges concerning MS4 requirements based on literature review, professional experience, and feedback solicited from stakeholders, municipal managers, and fellow professionals and offer real-world examples of efficient, effective MS4 frameworks and/or solutions. The five challenges are summarized as beliefs that: (1) agricultural land use is the largest pollutant contributor and the root cause of pollution problems; (2) stormwater management only benefits downstream communities; (3) large, expensive projects are required to comply with regulations; (4) maintenance, monitoring, and inspection of best management practices (BMPs) is overwhelmingly complex and expensive; and (5) a lack of direct funding makes complying with regulations an impossible task. These challenges are universal in nature for Phase II MS4 permittees and can create real barriers for effective stormwater management. However, we found many examples of methods or techniques to effectively address these five specific challenges, making them well-suited and important for discussion. BMPs can create tangible improvements for surrounding communities (e.g., reduced streambank erosion and flooding), and improved understanding of the structure and options within the MS4 program will help small municipalities make informed choices about management plans.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

How SARS-CoV-2 might affect potassium balance via impairing epithelial sodium channels? - Maryam Noori; Seyed Aria Nejadghaderi; Mark J. M. Sullman; Kristin Carson-Chahhoud; Mohammadreza Ardalan; Ali-Asghar Kolahi; Saeid Safiri (Molecular Biology Reports, 2021)

Association Between Greater Cerebellar Network Connectivity and Improved Phonemic Fluency Performance After Exercise Training in Older Adults - Junyeon Won; Yasmeen Faroqi-Shah; Daniel D. Callow; Allison Williams; Adewale Awoyemi; Kristy A. Nielson; J. Carson Smith (The Cerebellum, 2021)

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

Seawater transmission and infection dynamics of pilchard orthomyxovirus (POMV) in Atlantic salmon ( Salmo salar ) - Francisca Samsing; Megan Rigby; Hedda K. Tengesdal; Richard S. Taylor; Daniela Farias; Richard N. Morrison; Scott Godwin; Carla Giles; Jeremy Carson; Chloe J. English; Roger Chong; James W. Wynne (Journal of Fish Diseases, 2021)
The Tasmanian salmon industry had remained relatively free of major viral diseases until the emergence of pilchard orthomyxovirus (POMV). Originally isolated from wild pilchards, POMV is of concern to the industry as it can cause high mortality in farmed salmon ( Salmo salar ). Field observations suggest the virus can spread from pen to pen and between farms, but evidence of passive transmission in sea water was unclear. Our aim was to establish whether direct contact between infected and naïve fish was required for transmission, and to examine viral infection dynamics. Atlantic salmon post‐smolts were challenged with POMV by either direct exposure via cohabitation or indirect exposure via virus‐contaminated sea water. POMV was transmissible in sea water and direct contact between fish was not required for infection. Head kidney and heart presented the highest viral loads in early stages of infection. POMV survivors presented low viral loads in most tissues, but these remained relatively high in gills. A consistent feature was the infiltration of viral‐infected melanomacrophages in different tissues, suggesting an important role of these in the immune response to POMV. Understanding POMV transmission and host–pathogen interactions is key for the development of improved surveillance tools, transmission models and ultimately for disease prevention.

The microbiota influences the Drosophila melanogaster life history strategy - Amber W. Walters; Rachel C. Hughes; Tanner B. Call; Carson J. Walker; Hailey Wilcox; Samara C. Petersen; Seth M. Rudman; Peter D. Newell; Angela E. Douglas; Paul S. Schmidt; John M. Chaston (Molecular Ecology, 2020)
Organisms are locally adapted when members of a population have a fitness advantage in one location relative to conspecifics in other geographies. For example, across latitudinal gradients, some organisms may trade off between traits that maximize fitness components in one, but not both, of somatic maintenance or reproductive output. Latitudinal gradients in life history strategies are traditionally attributed to environmental selection on an animal's genotype, without any consideration of the possible impact of associated microorganisms (“microbiota”) on life history traits. Here, we show in Drosophila melanogaster , a key model for studying local adaptation and life history strategy, that excluding the microbiota from definitions of local adaptation is a major shortfall. First, we reveal that an isogenic fly line reared with different bacteria varies the investment in early reproduction versus somatic maintenance. Next, we show that in wild fruit flies, the abundance of these same bacteria was correlated with the latitude and life history strategy of the flies, suggesting geographic specificity of the microbiota composition. Variation in microbiota composition of locally adapted D. melanogaster could be attributed to both the wild environment and host genetic selection. Finally, by eliminating or manipulating the microbiota of fly lines collected across a latitudinal gradient, we reveal that host genotype contributes to latitude‐specific life history traits independent of the microbiota and that variation in the microbiota can suppress or reverse the differences between locally adapted fly lines. Together, these findings establish the microbiota composition of a model animal as an essential consideration in local adaptation.

Macrophage lipid accumulation in the presence of immunosuppressive drugs mycophenolate mofetil and cyclosporin A - Iryna Voloshyna; Isaac Teboul; Lora J. Kasselman; Michael Salama; Steven E. Carsons; Joshua DeLeon; Joseph Mattana; Nobuyuki Miyawaki; Allison B. Reiss (Inflammation Research, 2019)

Comparing the accuracy of estimated terrain elevations across spatial resolution - Mehran Ghandehari; Barbara P. Buttenfield; Carson J. Q. Farmer (International Journal of Remote Sensing, 2019)

Interlimb transfer and generalisation of learning in the context of persistent failure to accomplish a visuomotor task - D. A. E. Bolton; A. R. Buick; T. J. Carroll; R. G. Carson (Experimental Brain Research, 2019)

Consumption explains intraspecific variation in nutrient recycling stoichiometry in a desert fish - Eric K. Moody; Evan W. Carson; Jessica R. Corman; Hector Espinosa‐Pérez; Jorge Ramos; John L. Sabo; James J. Elser (Ecology, 2018)
Consumer‐driven nutrient recycling can have substantial effects on primary production and patterns of nutrient limitation in aquatic ecosystems by altering the rates as well as the relative supplies of the key nutrients nitrogen (N) and phosphorus (P). While variation in nutrient recycling stoichiometry has been well‐studied among species, the mechanisms that explain intraspecific variation in recycling N:P are not well‐understood. We examined the relative importance of potential drivers of variation in nutrient recycling by the fish Gambusia marshi among aquatic habitats in the Cuatro Ciénegas basin of Coahuila, Mexico. There, G. marshi inhabits warm thermal springs with high predation pressure as well as cooler, surface runoff‐fed systems with low predation pressure. We hypothesized that variation in food consumption among these habitats would drive intraspecific differences in excretion rates and N:P ratios. Stoichiometric models predicted that temperature alone should not cause substantial variation in excretion N:P, but that further reducing consumption rates should substantially increase excretion N:P. We performed temperature and diet ration manipulation experiments in the laboratory and found strong support for model predictions. We then tested these predictions in the field by measuring nutrient recycling rates and ratios as well as body stoichiometry of fish from nine sites that vary in temperature and predation pressure. Fish from warm, high‐predation sites excreted nutrients at a lower N:P ratio than fish from cool, low‐predation sites, consistent with the hypothesis that reduced consumption under reduced predation pressure had stronger consequences for P retention and excretion among populations than did variation in body stoichiometry. These results highlight the utility of stoichiometric models for predicting variation in consumer‐driven nutrient recycling within a phenotypically variable species.

Same habitat, different species: otolith microchemistry relationships between migratory and resident species support interspecific natal source classification - Carson G. Prichard; Jory L. Jonas; James J. Student; Nicole M. Watson; Kevin L. Pangle (Environmental Biology of Fishes, 2018)

Dietary lipophilic iron accelerates regional brain iron-load in C57BL6 mice - Douglas G. Peters; Carson J. Purnell; Michael P. Haaf; Qing X. Yang; James R. Connor; Mark D. Meadowcroft (Brain Structure and Function, 2018)

Interleukin-13 stimulates production of nitric oxide in cultured human nasal epithelium - Johnny L. Carson; Michelle Hernandez; Ilona Jaspers; Katherine Mills; Luisa Brighton; Haibo Zhou; Jing Zhang; Milan J. Hazucha (In Vitro Cellular & Developmental Biology - Animal, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Zooplankton ecology and trophic resources for rearing native fish on an agricultural floodplain in the Yolo Bypass California, USA - Nicholas J. Corline; Ted Sommer; Carson A. Jeffres; Jacob Katz (Wetlands Ecology and Management, 2017)

Aflatoxin contamination in corn sold for wildlife feed in texas - Nicholas R. Dunham; Steven T. Peper; Carson D. Downing; Ronald J. Kendall (Ecotoxicology, 2017)

Soil microbial communities alter leaf chemistry and influence allelopathic potential among coexisting plant species - Scott J. Meiners; Kelsey K. Phipps; Thomas H. Pendergast; Thomas Canam; Walter P. Carson (Oecologia, 2017)

Erratum to: Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Andrew Leis; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Estimating stormwater runoff for community gardens in New York City - Mara Gittleman; Carson J. Q. Farmer; Peleg Kremer; Timon McPhearson (Urban Ecosystems, 2017)

Reduced white matter MRI transverse relaxation rate in cognitively normal H63D-HFE human carriers and H67D-HFE mice - Mark D. Meadowcroft; Jianli Wang; Carson J. Purnell; Douglas G. Peters; Paul J. Eslinger; Elizabeth B. Neely; David J. Gill; Megha Vasavada; Fatima Ali-Rahmani; Qing X. Yang; James R. Connor (Brain Imaging and Behavior, 2016)

Foliar bacteria and soil fertility mediate seedling performance: a new and cryptic dimension of niche differentiation - Eric A. Griffin; M. Brian Traw; Peter J. Morin; Jonathan N. Pruitt; S. Joseph Wright; Walter P. Carson (Ecology, 2016)
The phyllosphere (comprising the leaf surface and interior) is one of the world's largest microbial habitats and is host to an abundant and diverse array of bacteria. Nonetheless, the degree to which bacterial communities are benign, harmful, or beneficial to plants in situ is unknown. We tested the hypothesis that the net effect of reducing bacterial abundance and diversity would vary substantially among host species (from harmful to beneficial) and this would be strongly mediated by soil resource availability. To test this, we monitored tree seedling growth responses to commercial antibiotics among replicated resource supply treatments (N, P, K) in a tropical forest in Panama for 29 months. We applied either antibiotics or control water to replicated seedlings of five common tree species ( Alseis blackiana , Desmopsis panamensis , Heisteria concinna , Sorocea affinis , and Tetragastris panamensis ). These antibiotic treatments significantly reduced both the abundance and diversity of bacteria epiphytically as well as endophytically. Overall, the effect of antibiotics on performance was highly host specific. Applying antibiotics increased growth for three species by as much as 49% ( Alseis , Heisteria , and Tetragastris ), decreased growth for a fourth species by nearly 20% ( Sorocea ), and had no impact on a fifth species ( Desmopsis ). Perhaps more importantly, the degree to which foliar bacteria were harmful or not varied with soil resource supply. Specifically, applying antibiotics had no effect when potassium was added but increased growth rate by almost 40% in the absence of potassium. Alternatively, phosphorus enrichment caused the effect of bacteria to switch from being primarily beneficial to harmful or vice versa, but this depended entirely on the presence or absence of nitrogen enrichment (i.e., important and significant interactions). Our results are the first to demonstrate that the net effect of reducing the abundance and diversity of bacteria can have very strong positive and negative effects on seedling performance. Moreover, these effects were clearly mediated by soil resource availability. Though speculative, we suggest that foliar bacteria may interact with soil fertility to comprise an important, yet cryptic dimension of niche differentiation, which can have important implications for species coexistence.

Ranavirus could facilitate local extinction of rare amphibian species - Julia E. Earl; Jordan C. Chaney; William B. Sutton; Carson E. Lillard; Andrew J. Kouba; Cecilia Langhorne; Jessi Krebs; Rebecca P. Wilkes; Rachel D. Hill; Debra L. Miller; Matthew J. Gray (Oecologia, 2016)

Evaluating the ecological impacts of salvage logging: can natural and anthropogenic disturbances promote coexistence? - Alejandro A. Royo; Chris J. Peterson; John S. Stanovick; Walter P. Carson (Ecology, 2016)
Salvage logging following windthrow is common throughout forests worldwide even though the practice is often considered inimical to forest recovery. Because salvaging removes trees, crushes seedlings, and compacts soils, many warn this practice may delay succession, suppress diversity, and alter composition. Here, over 8 yr following windthrow, we experimentally evaluate how salvaging affects tree succession across 11 gaps in Eastern deciduous forests of Pennsylvania, wherein each gap was divided into salvaged and control (unsalvaged) halves. Our gaps vary in size and windthrow severity, and we explicitly account for this variation as well as variation in soil disturbance (i.e., scarification) resulting from salvaging so that our results would be generalizable. Salvage logging had modest and ephemeral impacts on tree succession. Seedling richness and density declined similarly over time in both salvaged and unsalvaged areas as individuals grew into saplings. The primary impact of salvaging on succession occurred where salvaging scarified soils. Here, salvaging caused 41 to 82% declines in sapling abundance, richness, and diversity, but these differences largely disappeared within 5 yr. Additionally, we documented interactions between windthrow severity and scarification. Specifically, low‐severity windthrow and scarification combined reinforced dominance by shade‐tolerant and browse‐tolerant species ( Acer pensylvanicum, Fagus grandifolia ). In contrast, high windthrow severity and scarification together reduced the density of a fast‐growing pioneer tree ( Prunus pensylvanica ) and non‐tree vegetation cover by 75% and 26%, respectively. This reduction enhanced the recruitment of two mid‐successional tree species, Acer rubrum and Prunus serotina , by 2 and 3‐fold, respectively. Thus, our findings demonstrate that salvaging creates novel microsites and mitigates competing vegetation, thereby enhancing establishment of important hardwoods and promoting tree species coexistence. Our results, coupled with an assessment of 27 published post‐windthrow salvage studies, suggest short‐term studies may overestimate the impact of salvaging on regeneration. We conclude that the ecological costs and benefits of salvaging depend upon the variation in canopy and soil disturbance severity as well as the timescale at which effects are evaluated. Thus, our findings are inconsistent with the view that salvaging inexorably undermines plant diversity; rather we suggest salvaging can promote tree species coexistence within various contexts.

Pre‐Columbian ring ditch construction and land use on a ‘chocolate forest island’ in the Bolivian Amazon - John F. Carson; Francis E. Mayle; Bronwen S. Whitney; José Iriarte; J. Daniel Soto (Journal of Quaternary Science, 2016)
We present a palaeoecological investigation of pre‐Columbian land use in the savanna ‘forest island’ landscape of the north‐east Bolivian Amazon. A 5700‐year sediment core from La Luna Lake, located adjacent to the La Luna forest island site, was analysed for fossil pollen and charcoal. We aimed to determine the palaeoenvironmental context of pre‐Columbian occupation on the site and assess the environmental impact of land use in the forest island region. Evidence for anthropogenic burning and Zea mays L. cultivation began ∼2000 cal a BP, at a time when the island was covered by savanna, under drier‐than‐present climatic conditions. After ∼1240 cal a BP burning declined and afforestation occurred. We show that construction of the ring ditch, which encircles the island, did not involve substantial deforestation. Previous estimates of pre‐Columbian population size in this region, based upon labour required for forest clearance, should therefore be reconsidered. Despite the high density of economically useful plants, such as Theobroma cacao , in the modern forest, no direct pollen evidence for agroforestry was found. However, human occupation is shown to pre‐date and span forest expansion on this site, suggesting that here, and in the wider forest island region, there is no truly pre‐anthropogenic ‘pristine’ forest.

Coastal sea level changes, observed and projected during the 20th and 21st century - M. Carson; A. Köhl; D. Stammer; A. B. A. Slangen; C. A. Katsman; R. S. W. van de Wal; J. Church; N. White (Climatic Change, 2016)

Development and application of molecular methods ( PCR ) for detection of Tasmanian Atlantic salmon reovirus - S C Zainathan; G Carlile; J Carson; K A McColl; M St. J Crane; L M Williams; J Hoad; N J G Moody; H M Aiken; G F Browning; B F Nowak (Journal of Fish Diseases, 2015)
Molecular ( PCR ) diagnostic tests for the detection and identification of aquareovirus in general, and Tasmanian Atlantic salmon reovirus ( TSRV ) specifically, were developed, and their diagnostic sensitivity and specificity were determined and compared with virus isolation in cell culture. Intralaboratory and interlaboratory comparison of PCR (conventional hemi‐nested RT‐PCR & RT ‐ qPCR ) and virus isolation in cell culture using finfish cell lines, CHSE ‐214 and EPC , was carried out for the detection and identification of TSRV using field samples of farmed Atlantic salmon Salmo salar, L. from various aquaculture sites around Tasmania. The interlaboratory comparison of diagnostic methods was carried out between two laboratories, AAHL ‐ CSIRO and DPIPWE ‐Tasmania. A total of 144 fish from nine sites (12–33 fish per site) were sampled from two regions of Tasmania (Tamar River estuary in the north and Huon River estuary in the south‐east) during late spring to early summer of 2009, and the data were analysed using different statistical approaches. The prevalence of TSRV ranged from 6% to 22% in both regions. All the diagnostic methods (data from both laboratories) had high specificity, while the estimated sensitivity varied between tests with RT ‐ qPCR being the most sensitive (95.2%) method followed by virus isolation and then conventional hemi‐nested RT‐PCR .

Combination paracetamol and ibuprofen for pain relief after oral surgery: a dose ranging study - Hartley C. Atkinson; John Currie; John Moodie; Simon Carson; Steven Evans; James P. Worthington; Leon J. Steenberg; Eileen Bisley; Chris Frampton (European Journal of Clinical Pharmacology, 2015)

Lithium carbonate in the management of cannabis withdrawal: a randomized placebo-controlled trial in an inpatient setting - Jennifer Johnston; Nicholas Lintzeris; David J. Allsop; Anastasia Suraev; Jessica Booth; Dean S. Carson; David Helliwell; Adam Winstock; Iain S. McGregor (Psychopharmacology, 2014)

Pasture succession in the Neotropics: extending the nucleation hypothesis into a matrix discontinuity hypothesis - Chris J. Peterson; Jerald J. Dosch; Walter P. Carson (Oecologia, 2014)

Conditions for the validity of SNP-based heritability estimation - James J. Lee; Carson C. Chow (Human Genetics, 2014)

Ecosystem classifications based on summer and winter conditions - Margaret E. Andrew; Trisalyn A. Nelson; Michael A. Wulder; George W. Hobart; Nicholas C. Coops; Carson J. Q. Farmer (Environmental Monitoring and Assessment, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Laboratory evaluation of sample collection methods (organs vs swabs) for T asmanian salmon reovirus detection in farmed A tlantic salmon, S almo salar L . - S C Zainathan; J Carson; M St J Crane; B F Nowak (Journal of Fish Diseases, 2013)
The use of swabs relative to organs as a sample collection method for the detection of Tasmanian salmon reovirus ( TSRV ) in farmed T asmanian A tlantic salmon, S almo salar L., was evaluated by RT ‐q PCR . Evaluation of individual and pooled sample collection (organs vs swabs) was carried out to determine the sensitivity of the collection methods and the effect of pooling of samples for the detection of TSRV . Detection of TSRV in individual samples was as sensitive when organs were sampled compared to swabs, and in pooled samples, organs demonstrated a sensitivity of one 10‐fold dilution higher than sampling of pooled swabs. Storage of swabs at 4 °C for t = 24 h demonstrated results similar to those at t = 0. Advantages of using swabs as a preferred sample collection method for the detection of TSRV compared to organ samples are evident from these experimental trials.

The Victoria and Birrindudu Basins, Victoria River region, Northern Territory, Australia: a SHRIMP U–Pb detrital zircon and Sm–Nd study - C. J. Carson (Australian Journal of Earth Sciences, 2013)

In Vitro and In Vivo Evaluation of a Water-in-Oil Microemulsion System for Enhanced Peptide Intestinal Delivery - Dongyun Liu; Taku Kobayashi; Steven Russo; Fengling Li; Scott E. Plevy; Todd M. Gambling; Johnny L. Carson; Russell J. Mumper (The AAPS Journal, 2013)

Population structure in Chilean hake Merluccius gayi as revealed by mitochondrial DNA sequences - R. R. Vidal; E. W. Carson; J. R. Gold (Journal of Fish Biology, 2012)
Genetic variation and divergence among samples of Chilean hake Merluccius gayi , from three localities off the coast of Chile and one locality off the coast of northern Peru, were assessed using sequences from the control region of mitochondrial DNA. Homogeneity tests revealed occurrence of at least three distinct genetic stocks of M. gayi within the region sampled. Factors potentially contributing to genetic divergence among M. gayi probably include hydrodynamics and behaviour.

Training-induced modifications of corticospinal reactivity in severely affected stroke survivors - Ruth N. Barker; Sandra G. Brauer; Benjamin K. Barry; Toby J. Gill; Richard G. Carson (Experimental Brain Research, 2012)

Relationships between spatio‐temporal environmental and genetic variation reveal an important influence of exogenous selection in a pupfish hybrid zone - EVAN W. CARSON; MICHAEL TOBLER; W. L. MINCKLEY; RYAN J. AINSWORTH; THOMAS E. DOWLING (Molecular Ecology, 2012)
The importance of exogenous selection in a natural hybrid zone between the pupfishes Cyprinodon atrorus and Cyprinodon bifasciatus was tested via spatio‐temporal analyses of environmental and genetic change over winter, spring and summer for three consecutive years. A critical influence of exogenous selection on hybrid zone regulation was demonstrated by a significant relationship between environmental (salinity and temperature) and genetic (three diagnostic nuDNA loci) variation over space and time (seasons) in the Rio Churince system, Cuatro Ciénegas, Mexico. At sites environmentally more similar to parental habitats, the genetic composition of hybrids was stable and similar to the resident parental species, whereas complex admixtures of parental and hybrid genotypic classes characterized intermediate environments, as did the greatest change in allelic and genotypic frequencies across seasons. Within hybrids across the entire Rio Churince system, seasonal changes in allelic and genotypic frequencies were consistent with results from previous reciprocal transplant experiments, which showed C. bifasciatus to suffer high mortality (75%) when exposed to the habitat of C. atrorus in winter (extreme temperature lows and variability) and summer (abrupt salinity change and extreme temperature highs and variability). Although unconfirmed, the distributional limits of C. atrorus and C. atrorus ‐like hybrids appear to be governed by similar constraints (predation or competition). The argument favouring evolutionary significance of hybridization in animals is bolstered by the results of this study, which links the importance of exogenous selection in a contemporary hybrid zone between C. atrorus and C. bifasciatus to previous demonstration of the long‐term evolutionary significance of environmental variation and introgression on the phenotypic diversification Cuatro Ciénegas Cyprinodon .

Delivery of Water-Soluble Drugs Using Acoustically Triggered Perfluorocarbon Double Emulsions - Mario L. Fabiilli; James A. Lee; Oliver D. Kripfgans; Paul L. Carson; J. Brian Fowlkes (Pharmaceutical Research, 2010)

A simultaneous test of trophic interaction models: which vegetation characteristic explains herbivore control over plant community mass? - James Patrick Cronin; Stephen J. Tonsor; Walter P. Carson (Ecology Letters, 2010)
Ecology Letters (2010) 13: 202–212 Abstract Predicting herbivore control over plants (i.e. changes in plant mass due to herbivore damage) is a central goal of ecology. Progress has been limited, however, because the vegetation characteristics thought to influence herbivore control are naturally correlated and typically experimentally confounded. To address this problem, we defined eight conventional models that predict herbivore control over plant community mass, each model based on a different vegetation characteristic (i.e. host concentration, tissue nitrogen, growth rate, size, tolerance of herbivory or net primary productivity). We then used structural equation modelling to test each model against two field experiments. Our results clearly rejected all models except for a tolerance of herbivory mechanism; stems with greater access to limiting resources better tolerated herbivory, regardless of where herbivore activity was greatest. Consequently, herbivore reductions of plant community mass were greatest at low resource availability. This adds to evidence that herbivore activity poorly predicts herbivore control.

Determination of the compositional change (1999–2006) in the pine forests of British Columbia due to mountain pine beetle infestation - Colin Robertson; Carson J. Q. Farmer; Trisalyn A. Nelson; Ian K. Mackenzie; Michael A. Wulder; Joanne C. White (Environmental Monitoring and Assessment, 2009)

Microsatellite markers for species of the genus Dionda (Cyprinidae) from the American southwest - Mark A. Renshaw; Evan W. Carson; Ashley H. Hanna; Caird E. Rexroad; Trevor J. Krabbenhoft; John R. Gold (Conservation Genetics, 2009)

Effect of extracellular products of Tenacibaculum maritimum in Atlantic salmon, Salmo salar L. - R Van Gelderen; J Carson; B Nowak (Journal of Fish Diseases, 2009)

What signs and symptoms would be expected after ingestion of this plant? - Samuel J. Stellpflug; Carson R. Harris (Journal of Medical Toxicology, 2009)

Muscle wasting and interleukin-6-induced atrogin-I expression in the cachectic Apc Min/+ mouse - Kristen A. Baltgalvis; Franklin G. Berger; Maria Marjorette O. Peña; J. Mark Davis; James P. White; James A. Carson (Pflügers Archiv - European Journal of Physiology, 2009)

BACE1 Polymorphisms Do Not Influence Platelet Membrane β-secretase Activity or Genetic Susceptibility for Alzheimer’s Disease in the Northern Irish Population - S. Todd; A. J. McKnight; W. W. Liu; R. Carson; S. Heggarty; B. McGuinness; G. B. Irvine; D. Craig; A. P. Passmore; J. A. Johnston (NeuroMolecular Medicine, 2008)

Ephemeral floodplain habitats provide best growth conditions for juvenile Chinook salmon in a California river - Carson A. Jeffres; Jeff J. Opperman; Peter B. Moyle (Environmental Biology of Fishes, 2008)

Neuromuscular and biomechanical factors codetermine the solution to motor redundancy in rhythmic multijoint arm movement - Aymar de Rugy; Stephan Riek; Yalchin Oytam; Timothy J. Carroll; Rahman Davoodi; Richard G. Carson (Experimental Brain Research, 2008)

Evaluating the post-release efficacy of invasive plant biocontrol by insects: a comprehensive approach - Walter P. Carson; Stephen M. Hovick; Anthony J. Baumert; Daniel E. Bunker; Thomas H. Pendergast (Arthropod-Plant Interactions, 2008)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

The neurocognitive effects of aripiprazole: an open-label comparison with olanzapine - Robert S. Kern; Michael F. Green; Barbara A. Cornblatt; J. Randall Owen; Robert D. McQuade; William H. Carson; Mirza Ali; Ron Marcus (Psychopharmacology, 2006)

Movement of Sacramento Sucker, Catostomus occidentalis, and Hitch, Lavinia exilicauda, during a Spring Release of Water from Camanche Dam in the Mokelumne River, California - Carson A. Jeffres; A. Peter Klimley; Joseph E. Merz; Joseph J. Cech (Environmental Biology of Fishes, 2006)

Effects of paroxetine on cardiovascular response to mental stress in subjects with a history of coronary artery disease and no psychiatric diagnoses - Michael Golding; Michael Kotlyar; Stanley W. Carson; Sherri Hoyler; Cindy Lazarus; Colin Davidson; Joseph Guzzo; Eric Sontz; J. C. Garbutt (Psychopharmacology, 2005)

QTL associations for density and diameter in Pinus radiata and the potential for marker-aided selection - M. E. Devey; S. D. Carson; M. F. Nolan; A. C. Matheson; C. Te Riini; J. Hohepa (Theoretical and Applied Genetics, 2004)

Governing coordination: behavioural principles and neural correlates - R. G. Carson; J. A. S. Kelso (Experimental Brain Research, 2004)

Presence of anti‐ Neoparamoeba sp. antibodies in Tasmanian cultured Atlantic salmon, Salmo salar L. - K Gross; J Carson; B Nowak (Journal of Fish Diseases, 2004)
Previous studies have indicated that when Atlantic salmon, Salmo salar L., are exposed to Neoparamoeba sp. the fish produce anti‐ Neoparamoeba sp. antibodies. It appears unlikely that these antibodies elicit any specific protection against amoebic gill disease (AGD) as fish with demonstrable activities have been affected by AGD. Experiments were conducted on Atlantic salmon cultured throughout Tasmania to assess the natural production of antibodies towards Neoparamoeba sp. Fish were sampled from areas where AGD was prevalent and from areas where there had been no reported cases. An enzyme‐linked immunosorbent assay (ELISA) was used to measure anti‐ Neoparamoeba sp. antibody activities in serum. All fish from sea water had antibody activities greater than the negative control fish, including fish from areas with no reported cases of AGD. Time trial samples indicated that time after transfer to sea water did not appear to be a significant ( P > 0.05) factor in antibody activity, however location was ( P κ value, 0.16) between the ELISA result and the isolation of Neoparamoeba sp. from the gills of the same fish. The results suggest that Atlantic salmon in seawater culture in Tasmania produce anti‐ Neoparamoeba sp. antibodies regardless of infection history, suggesting the presence of Neoparamoeba sp. in the environment.

RhoA induction by functional overload and nandrolone decanoate administration in rat skeletal muscle - Joseph M. McClung; Won J. Lee; Raymond W. Thompson; Larry L. Lowe; James A. Carson (Pflügers Archiv - European Journal of Physiology, 2003)

Bimanual aiming and overt attention: one law for two hands - S. Riek; J. R. Tresilian; M. Mon-Williams; V. L. Coppard; R. G. Carson (Experimental Brain Research, 2003)

Coral‐reef sounds enable nocturnal navigation by some reef‐fish larvae in some places and at some times - J. M. Leis; B. M. Carson‐Ewart; A. C. Hay; D. H. Cato (Journal of Fish Biology, 2003)
At Lizard Island, Great Barrier Reef, catches of fish larvae by light traps that broadcast nocturnal reef sounds (noisy traps) were compared with catches by quiet traps over two 2·5 week new‐moon periods in November (XI) 2000 and January (I) 2001. Three areas were sampled: near‐reef (NR, 500 m from the shore) in I, middle (M, 650 m) in I and XI and offshore (O, >1000 m) in XI. The most abundant taxa captured were Apogonidae, Blenniidae, Chaetodontidae, Lethrinidae, Mullidae and Pomacentridae. Significant differences in catch were found between areas, and a position effect was found at the O and M areas. At the NR and M areas, no taxa had significantly greater catches in quiet traps, but larvae of five taxa had significantly greater catches in noisy traps. These were (areas and times of greater catches): Apogonidae (NR; M XI), Mullidae (M I & XI), Pomacentridae (NR; M I & XI), Serranidae (M I) and Sphyraenidae (NR). At the offshore area, five taxa (Apogonidae, Blenniidae, Chaetodontidae, Mullidae and Pomacentridae) had significantly greater catches in quiet traps and only Lethrinidae had significantly greater catches in noisy traps. Thus some taxa (particularly apogonids and pomacentrids which had catches up to 155% greater in noisy traps, but also lethrinids and mullids, and perhaps others), were attracted to reef sounds at night, but this apparently varied with location and time. The sound‐enhanced catches imply a radius of attraction of the sound 1·02–1·6 times that of the light. More than 65 m from the speaker,the broadcast sound levels at frequencies typical of fish hearing were equivalent to background levels, providing a maximum radius of sound attraction in this experiment.

Temporal and spatial distribution of paramoebae in the water column – a pilot study - G M Douglas‐Helders; D P O'Brien; B E McCorkell; D Zilberg; A Gross; J Carson; B F Nowak (Journal of Fish Diseases, 2003)
Amoebic gill disease is the main disease affecting the salmonid industry in Tasmania, but no information on the distribution of the causative pathogen, Neoparamoeba pemaquidensis , in the aquatic environment is available. This pilot study aimed to determine temporal and spatial distributions of paramoebae species in the water column, using an immuno‐dot blot technique. Water samples were collected from inside fish cages at various depths (0.5, 5.5 and 11.0 m) in both summer and winter, as well as various distances (0, 0.5, 240, 280, 750 and 1100 m) away from the sea cage and farming site. Paramoebae densities were estimated using the most probable number technique (MPN). Temperature, salinity, dissolved oxygen, turbidity, nitrite and nitrates, and bacterial counts were measured for each water sample. Data were analysed using a residual maximum likelihood test and significant associations between paramoebae densities and environmental factors were analysed. Results showed that densities were significantly higher in summer ( P = 0.017), at 5.5 m depth ( P = 0.029), and reduced to the lowest density at 1100 m away from the cage sites ( P = 0.008). Bacterial counts, turbidity and temperature were found to be significantly associated with paramoebae densities.

Wild fish are not a significant reservoir for Neoparamoeba pemaquidensis (Page, 1987) - G M Douglas‐Helders; D R Dawson; J Carson; B F Nowak (Journal of Fish Diseases, 2002)
Amoebic gill disease (AGD), caused by the protozoan Neoparamoeba pemaquidensis (Page, 1987) is the most important disease affecting salmon farms in Tasmania. Reservoirs for this protozoan parasite are largely unknown. This study investigated wild fish as a potential reservoir of N. pemaquidensis . A total of 325 wild fish, comprising 12 different fish species, were caught from and around salmon farms and examined for the presence of AGD. None of the wild fish were infected with AGD. In a laboratory trial, seahorse, Hippocampus abdominalis , greenback flounder, Rhombosolea tapirina, and Atlantic salmon, Salmo salar, were challenged with N. pemaquidensis . Neoparamoeba pemaquidensis was detected on the gills on 10 of 15 (66.7%) flounder, nine of 24 (37.5%) seahorses, and six of six (100%) Atlantic salmon. However, paramoebae positive flounder and seahorse lacked the characteristic AGD gill pathology. It is concluded that AGD does not appear in wild fish and wild fish do not seem to be a reservoir of the pathogen.

In situ settlement behaviour of damselfish (Pomacentridae) larvae - J. M. Leis; B. M. Carson‐Ewart (Journal of Fish Biology, 2002)
Settlement‐stage damselfish (Pomacentridae) larvae of 13 species in seven genera were obtained from light traps at Lizard Island, Great Barrier Reef, Australia. Behaviour, observed in situ by SCUBA divers, of 245 larvae (6–13 mm, L S ; 5–60 individuals per species) released individually within a few m of reefs during the day differed markedly among species. From 0–28% (range among 13 species) of individuals of each species swam away from the adjacent reefs without swimming to the reefs. Of those that swam to a reef, 0–75% settled. For three species, sufficient data were available to test the hypothesis that these percentages did not differ amongst reefs: the hypothesis was rejected in one species. From 0–75% of larvae that reached the reef were eaten, 0–63% subsequently left the reef and 0–60% were still swimming over the reef at the end of the observation period. Swimming speeds of all but one species were greater when swimming away from the reef than toward it. Most species exceeded average current speeds when swimming away from reefs, but not when swimming toward and over them. Average swimming depths were in the upper half of the water column for most species, and were somewhat greater where the water depths were greater. The time the larvae swam over the reef before settling and the distance swum varied greatly among species from 0 to a mean of 5.5 min and 43 m. Settlement habitats chosen differed amongst species, and in some species, they were very specific. Average settlement depth varied among species from 6–13.5 m. In one species, settlement depth varied between reefs. About half of the 53 observed interactions between larvae and reef resident fishes were predation attempts: fishes of eight species (six families) attacked larvae. The other interactions were aggressive approaches by 11 species of resident fishes, all but one of which were pomacentrids. Many of these aggressive interactions discouraged settlement attempts. Larvae of some species experienced no predatory or aggressive interactions, whereas in other species interactions averaged >0.6 per released larva. Species that swam more‐or‐less directly to settlement sites near the reef edge experienced more interactions. Even within the same family, settlement behaviour differed among species in nearly all measures.

Role of peripheral afference during acquisition of a complex coordination task - R. G. Carson; C. J. Smethurst; M. Forner; D. P. Meichenbaum; D. C. Mackey (Experimental Brain Research, 2002)

Neural compensation for compliant loads during rhythmic movement - Mackey D.; Meichenbaum D.; Shemmell J.; Riek S.; Carson R. (Experimental Brain Research, 2002)

Distribution of Mytilus edulis , M . galloprovincialis , and their hybrids in open-coast populations of mussels in southwestern England - Hilbish T.; Carson E.; Plante J.; Weaver L.; Gilg M. (Marine Biology, 2002)

Differential experimental micrometastasis to lung, liver, and bone with lacZ-tagged CWR22R prostate carcinoma cells - Julianne L. Holleran; Carson J. Miller; Nancy L. Edgehouse; Theresa P. Pretlow; Lloyd A. Culp (Clinical & Experimental Metastasis, 2002)

Development and validation of a new dot blot test for the detection of Paramoeba pemaquidensis (Page) in fish - M Douglas‐Helders; J Carson; T Howard; B Nowak (Journal of Fish Diseases, 2001)
In this study, the development of a dot blot assay to assess amoebic gill disease (AGD) using non‐lethal gill mucus samples is described and its performance validated by comparing the assay with the indirect fluorescent antibody test (IFAT), the ‘gold standard’ test. The agreement between the two tests was high, with a positive predictive value of 95% and negative predictive value of 93%, with a corrected κ value of 0.88. The sensitivity and specificity of the test were 97 and 91%, respectively. The dot blot is both sensitive and specific for Paramoeba pemaquidensis and is formatted so that large numbers of samples can be conveniently analysed.

Alleviation of aluminum toxicity to Rhizobium leguminosarum bv. viciae by the hydroxamate siderophore vicibactin - Nicola J. Rogers; Kerry C. Carson; Andrew R. Glenn; Michael J. Dilworth; Martin N. Hughes; Robert K. Poole (BioMetals, 2001)

Behaviour of pelagic larvae of four coral-reef fish species in the ocean and an atoll lagoon - J. Leis; B. Carson-Ewart (Coral Reefs, 2001)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Nocardiosis in tank‐reared Atlantic salmon, Salmo salar L. - M P. Bransden; J. Carson; B L. Munday; J H. Handlinger; C G. Carter; B F. Nowak (Journal of Fish Diseases, 2000)
Nocardiosis is an infection caused by aerobic Gram‐positive, branching, filamentous rods of the genus Nocardia . The organism is resident in both soil and plants ( Austin & Austin 1993 ; Frerichs 1993 ), and is closely related to Mycobacterium spp. Nocardiosis caused by Nocardia asteroides and N. seriolae (previously N. kampachi ) has been reported in several finfish species, both freshwater and marine. The first reported incidence was recorded by Valdez & Conroy (1963) in neon tetras, Hyphessobrycon innesi (Myers), and subsequently in other fish species, some of commercial significance including rainbow trout, Oncorhynchus mykiss (Walbaum) ( Snieszko, Bullock, Dunbar & Pettijohn 1964 ), brook trout, Salvelinus fontinalis (Mitchill), ( Campbell & MacKelvie 1968 ) and yellowtail, Seriola quinqueradiata (Temminck & Schlegel; Kubota, Kariya, Nakamura & Kira 1968 ). Despite two of these incidences occurring in salmonids, infection by Nocardia spp. in Atlantic salmon, Salmo salar L., has not previously been reported.

In situ swimming and settlement behaviour of larvae of an Indo-Pacific coral-reef fish, the coral trout Plectropomus leopardus (Pisces: Serranidae) - J. M. Leis; B. M. Carson-Ewart (Marine Biology, 1999)

Evidence for polynuclear iron(III) clusters in the root nodule bacterium, Rhizobium leguminosarum bv. viciae WSM710 - Timothy G. St. Pierre; Kerry C. Carson; John Webb; Andrew R. Glenn; Michael J. Dilworth (BioMetals, 1999)

Expression and chromosomal localization of the Requiem gene - Theodore G. Gabig; Colin D. Crean; Alison Klenk; Haiyan Long; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Danielle Quincey; Fabienne Parente; Françoise Lespinasse; Georges F. Carle; Patrick Gaudray; et al. (Mammalian Genome, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Specificity of siderophore-mediated transport of iron in rhizobia - K. C. Carson; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1994)

Specificity of siderophore-mediated transport of iron in rhizobia - K. C. Carson; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1994)

Siderophore and organic acid production in root nodule bacteria - K. C. Carson; S. Holliday; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1992)